BDNF-dependent consolidation of fear memories in the perirhinal cortex - Schulz-Klaus, Brigitte; Lessmann, Volkmar; Endres, Thomas (Frontiers in Behavioral Neuroscience, 2013)
In the recent years the perirhinal cortex (PRh) has been identified as a crucial brain area in fear learning. Since the neurotrophin BDNF (brain-derived neurotrophic factor) is an important mediator of synaptic plasticity and also crucially involved in memory consolidation of several learning paradigms, we analyzed now whether fear conditioning influences the expression of BDNF protein in the PRh. Here we observed a specific increase of BDNF protein 120 minutes after fear conditioning training. In order to test whether this increase of BDNF protein level is also required for the consolidation of the fear memory, we locally applied the Trk receptor inhibitor k252a into the PRh during this time window in a second series of experiments. By interfering with BDNF-TrkB-signaling during this critical time window, the formation of a long-term fear memory was completely blocked, indicated by a complete lack of fear potentiated startle one day later. In conclusion the present study further emphasizes the important role of the PRh in cued fear learning and identified BDNF as an important mediator for fear memory consolidation in the PRh.